Identification key to the species of genus Thrips (Thysanoptera, Thripidae) from India with three new species and one new record - Tyagi, Kaomud; Pal, Shash; Sarma, Madhurima; Kumar, Vikas (Zootaxa, 2025)
A revised key to 52 species of the genus Thrips recorded from India is provided, including two species from Nepal [Thrips meridionalis (Priesner) and Thrips tectus (zur Strassen)] and three new species: Thrips apricus sp. nov. from West Bengal, Thrips hemkundensis sp. nov. from Uttarakhand, and Thrips roseae sp. nov. from Himachal Pradesh. Thrips safrus Mound & Masumoto is first time reported from Punjab, India. We studied the type specimens of 19 species, and non-type specimens of 26 species, but 7 species are included in the key based on the original descriptions.